Market conditions, default risk and credit spreads - Dragon Yongjun Tang; Hong Yan (Deutsche Bundesbank, 2008)
This study empirically examine the impact of market conditions on credit spreads as motivated by recently developed structural credit risk models. Using credit default swap (CDS) spreads, we find that, in the time series, average credit spreads are decreasing in GDP growth rate, but increasing in GDP growth volatility. We document that credit spreads are lower when investor sentiment is high and when the systematic jump risk is low. In the cross section, we confirm that firm-level cash flow volatility raises credit spreads. More importantly, we demonstrate that the impact of market conditions on credit spreads is substantially affected by firm heterogeneity. During economic expansions, ceteris paribus, firms with high cash flow betas have lower credit spreads than those with low cash flow betas. This relation disappears during economic recessions, consistent with theoretical predictions. – – In diesem Arbeitspapier untersuchen wir empirisch, wie die gesamtwirtschaftlichen Bedingungen die Renditeabstände von Unternehmensanleihen, die mit einem Ausfallrisiko behaftet sind, beeinflussen. Dabei verwenden wir Spreads von Kreditausfallswaps (Credit Default Swap, CDS) als Näherungswert für Kreditspreads und stellen fest, dass die durchschnittlichen Kreditspreads im Zeitverlauf bei wirtschaftlicher Expansion niedriger und bei wirtschaftlicher Rezession höher sind. Wenn das Wirtschaftswachstum volatiler ist, führt dies ebenfalls zu höheren Kreditspreads. Wir stellen fest, dass Kreditspreads bei positiver Anlegerstimmung und geringem Risiko eines marktweiten Sprungs niedriger ausfallen. Firmenübergreifend stellen wir fest, dass ein auf Unternehmensebene volatiler Cashflow zu einer Erhöhung der Kreditspreads führt. Was noch entscheidender ist, wir zeigen, dass in Zeiten wirtschaftlicher Expansion ? bei ansonsten gleichen Bedingungen ? Unternehmen, deren Cashflow stark mit dem gesamtwirtschaftlichen Wachstum korreliert, geringere Kreditspreads aufweisen als solche mit einer schwachen Cashflow-Korrelation. Im Einklang mit den theoretischen Voraussagen verschwindet dieser Zusammenhang in Zeiten wirtschaftlicher Rezession.
Keywords: G13; G12; E44; E43; 330; Credit Risk; Credit Default Swaps; Credit Spreads; Market Conditions